Kenya Public Expenditure Review 2020 : Options for Fiscal Consolidation after the COVID-19 Crisis - World Bank (World Bank, Nairobi, 2020)
The objective of this public expenditure review (PER) is to provide the government with options for fiscal consolidation and support macroeconomic stability in the medium-term. This PER addresses the broad topic of expenditure efficiency and examines options for expenditure rationalization to help return Kenya’s fiscal accounts to a prudent trajectory in the medium-term. The PER is being undertaken as a programmatic analytical product with two modules. The first module focuses on identifying options for expenditure rationalization and measures to strengthen within-year expenditure control for better expenditure management. The second module to be delivered in FY21 will focus on efficiency, effectiveness, and equity of spending within public services delivery sectors of education, health, and disaster risk financing. The report builds upon several other Bank-led reports that contribute to the discussion around improving public expenditure and strengthening expenditure controls in Kenya. It complements an ongoing governance for enabling service delivery and public investments in Kenya (GESDeK) project, which is at the forefront in supporting numerous reforms highlighted in this PER to improve efficiency in spending and strengthen expenditure controls. The report is organized as follows: chapter one contains the macro context, trends, and composition of spending, overall balance and debt. Chapter two contains the fiscal and debt sustainability analysis while chapter three presents options for expenditure rationalization in Kenya. Chapter four ties it all together with fiscal savings and policy recommendations.